2018
DOI: 10.1111/acfi.12349
|View full text |Cite
|
Sign up to set email alerts
|

Operating cash flow asymmetric timeliness in Australia

Abstract: Operating cash flow (CFO) asymmetric timeliness occurs when CFO reflects bad news more quickly than good news. We examine the presence and determinants of CFO asymmetric timeliness in Australia, where substantial differences in reporting requirements of cash flow components, in characteristics of listed companies and in the degree of conservative financial reporting produce contrasting findings to those in the United States. We find supportive evidence for the novel 'sticky cost behaviour' explanation and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Recent cost stickiness research (in green and yellow) shows areas related to research in the government sector (Bradbury & Scott, 2018;Cohen et al, 2017;Wu et al, 2020), stateowned enterprises (Jiang et al, 2016;Z. Li et al, 2020;Prabowo et al, 2018;Zhong & Gao, 2017) and cost stickiness research in the area of business strategy (Ballas et al, 2020;Lu et al, 2020;Xu & Zheng, 2020). In addition, the latest cost stickiness research also examines the role of CEOs in causing cost stickiness (Khedmati et al, 2019;Lai et al, 2021;Lee et al, 2019;Li et al, 2020;Lopatta et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Recent cost stickiness research (in green and yellow) shows areas related to research in the government sector (Bradbury & Scott, 2018;Cohen et al, 2017;Wu et al, 2020), stateowned enterprises (Jiang et al, 2016;Z. Li et al, 2020;Prabowo et al, 2018;Zhong & Gao, 2017) and cost stickiness research in the area of business strategy (Ballas et al, 2020;Lu et al, 2020;Xu & Zheng, 2020). In addition, the latest cost stickiness research also examines the role of CEOs in causing cost stickiness (Khedmati et al, 2019;Lai et al, 2021;Lee et al, 2019;Li et al, 2020;Lopatta et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A total of two articles were conceptual papers Guenther et al, 2014), and 24 articles did not discuss the determinants of cost stickiness but instead used them as independent variables. These articles have not been used because they discuss the effects of cost stickiness on, for example, the forecasting of earnings (Ciftci et al, 2016;Ciftci & Salama, 2018;Kaspereit & Lopatta, 2019;Lopatta et al, 2020;Lu et al, 2020;Tang et al, 2020;Weiss, 2010). Be cause our focus is the managers' behaviour, we have dropped 15 articles that discuss, for example, the effect of an auditor's choice, ac counting policies, changes in office address, CEO structure, and changes in the research sample on cost stickiness (Chae & Chung, 2015;Chae & Ryu, 2016;Chung et al, 2019;Ibrahim, 2018;Lee et al, 2019;Loy & Hartli eb, 2018;Shust & Weiss, 2014;Xue & Hong, 2016;Yang, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…As users of cost account ing information, we need to understand the causes of the asymmetry of cost behaviour, especially cost stickiness. Studies have even shown that cost stickiness (CS) affects the company's stock performance (Ciftci et al, 2016;Ciftci & Salama, 2018;Kaspereit & Lopatta, 2019;Lopatta et al, 2020;Lu et al, 2020;Tang et al, 2020;Weiss, 2010). The asymmetry of cost behaviour is due to individual management considerations in ma king decisions.…”
mentioning
confidence: 99%
“…In addition, we explore whether the effect of Guba messages is conditional on the narrative tone of the messages to further substantiate their role of information dissemination. Negative narrative tone in corporate disclosures and media reports are found to contain more information contents and thus have significantly higher effect on share price performance, compared to messages with positive tone (Ahmad et al, 2016; An et al, 2020; Jiang et al, 2016; Lu et al, 2020; Zhai et al, 2021). Similarly, negative Guba messages can reflect more firm‐specific information than positive messages since managers tend to release good news immediately but withhold bad news (Bertomeu et al, 2020; Kothari et al, 2009).…”
Section: Guba Messages and Stock Price Synchronicity: Possible Mechan...mentioning
confidence: 99%